Pintura para catálogos: Notas sobre o arquivamento da arte - Helio Alvarenga Nunes (2009)
From the study of clearly institutional exhibition catalogs according to the relationship they produce in the library, this study introduces the concept / teaser painting for catalogs and checks its possibility retaking the discussion of art as photography, neglected in its most universaloutbreak. From the photographed painting and the perception that the museum succumbs to an array of values which edge is the value of archiving, seeks to determine the characteristics of the new relationship of art to its archive in our digital age, bringing a problem into this relationship according to non-conciliatory dialectics, inspired by Benjamin, always looking for the prospect of reanimation before the reification which gets only partial success.For this, this study operationalizes the concept of Malraux's musée imaginaire, defending it against Crimps criticism, transporting it to the present time, sharpening its duplicity and reworking the concepts of resurrection and photographic recreation to propose an engagementwhich is to continue producing (concept derived from Foster) an art characterized by the diffusion (light metaphor) and diminution (concept derived from Benjamin). This production is marked by the possibility of a double substitution with a concomitant double registration of the artwork, which makes the distinction between original and copy unimportantand even undesirable, since the original values defense generally guarantees the free movement of power-knowledge in diagrammatic spaces identified as catalog factories. To probe the operation of these factories and propose leaks, build another catalog definition based onthe archive concept, according to Derridas and Foucaults concepts, and searching for usage alternatives. It explicits, then these issues in the artistic context of Belo Horizonte, using some artists texts marked by informality.